THE GENERAL OVERVIEW OF CORONOMIC PROCESSES AND MAIN DIRECTIONS OF PROBLEM SOLVING (Globalization and Business, 2023)
The COVID-19 new coronavirus-related pandemic processes have had a significant impact on the world’s economy. Due to the fact that the assessment of coronavirus results requires an important analytical approach, a completely new term has been proposed by science - coronomics, the subject of which is the negative impact of coronavirus on various sectors of the economy. The term coronomics was introduced by Sri Lankan professor Ajith De Alwis. The COVID-19-related pandemic process directly increases coronomic urgency gradually. It could be highlighted, that similar types of global risks will always exist. Understanding this is very important for society in their daily life and in planning the economic projects that should be implemented in the future.  Nowadays, humankind is facing a completely new global economic crisis, the causes of which are provoked by factors outside the economy (coronavirus). A clear example of this is the difficulties that have affected the economies of both China and a number of leading European countries. A number of companies have closed in China, the world's second-largest economy. A similar situation has arisen in the EU. Due to the arising circumstances, the mechanisms and tools that were actively used during the global financial and economic crisis of 2008-2009 are mainly considered in the fight against the coronary crisis. It should be noted that the current crisis is extremely different from the events that happened in 2008-2009 when the origin of the crisis was purely economic and not medical-biological. The spread up of pandemic processes directly influenced new technological challenges, especially in terms of the development of various types of applications and software packages. Therefore, digital-based industries play a more and more important role in society. Noteworthy that the needs of society, along with technological development, are undergoing a fundamental change, and therefore, to meet them, it is necessary to develop completely different, innovative technologies based on high technology. The creation of social networks has had a significant impact on technological development. A social network is a means by which new, completely different industries are formed. In addition to the above, lately, more and more people are talking about blockchain technologies and their perspectives, through which it is possible to develop various industries through online technologies, which becomes especially relevant in late 2019 and early 2020 when the COVID-19 new coronavirus pandemic spread worldwide.